Understanding English Texts for Non-English Students: Reading Habits and Reading Preferences in Az-Zainiyah Nurul Jadid - Ekowijayanto, Mochlis; Astutik, Yayuk; Khomariyah, Nur (Universitas Nurul Jadid, 2021)
The role of students in Indonesia is needed, especially their ideas and opinions to develop this country. The quality of human resources is certainly very relevant to students' interest in reading. Reading habits are not only related to the teaching and learning process, but also can shape the personality of an individual by living the reading results. The research aims to study the process of reading habits and reading preferences favored by students. The research method used was a descriptive survey involving 45 students of non-English students in Az-Zainiyah Nurul Jadid. In obtaining data to find out the problems faced by students in understanding English reading texts, a questionnaire was used relating to reading habits and reading preferences. The findings from this study are expected to be used as an evaluation material that reading skills also need to be introduced further to students so that they can use them in the reading process.